LOXL2 Expression Status Is Correlated With Molecular Characterizations of Cervical Carcinoma and Associated With Poor Cancer Survival via Epithelial-Mesenchymal Transition (EMT) Phenotype - Cao, Canhui; Lin, Shitong; Zhi, Wenhua; Lazare, Cordelle; Meng, Yifan; Wu, Ping; Gao, Peipei; Wei, Juncheng; Wu, Peng (Frontiers in Oncology, 2020)
As molecular analyses based on high-throughput sequencing have developed, the molecular classification of cancer has facilitated clinical work. The aim of the present study was to identify a new potential therapeutic target for cervical carcinoma by molecular analyses. We firstly detected the expression pattern of LOXL2 in 50 paired normal cervix and cervical carcinoma via qPCR and immunohistochemistry, and the LOXL2 expression pattern was found to be in accordance with public datasets from Gene Expression Omnibus (GEO). Then, we comprehensively rewired the 176 cervical carcinoma samples from The Cancer Genome Atlas (TCGA), subsequently clustered the samples into two groups corresponding to LOXL2 expression to determined the associations between LOXL2 expression status and molecular characterizations of cervical carcinoma. In vitro assays for further verifying the correlations in SiHa-shLOXL2 and HeLa-shLOXL2 cell lines. In this study, we found that LOXL2 highly expressed in carcinoma tissue, with 14 CpG islands of LOXL2 promoter that were significantly and negatively associated with its expression in cervical carcinoma. And there were notable correlations among LOXL2 expression status and molecular characterizations of cervical carcinoma, including diagnostic age, HPV A7 types, mRNA molecular clusters, miRNA molecular clusters, and DNA methylation molecular clusters et al. In addition, high LOXL2 expression status was negatively correlated with lower tumor mutation density, especially in EP300, ERBB2, EGFR and NOTCH2, and was negatively correlated with lower expression of APOBEC3 family genes, such as APOBEC3A, APOBEC3B, APOBEC3D and APOBEC3G. Furthermore, high LOXL2 expression was associated with poor overall (OS) and poor disease-free survival (DFS) in cervical carcinoma, and was associated with higher epithelial-mesenchymal transition (EMT) score, enrichment of extracellular matrix (ECM) signaling, the phenotype that was found to be associated with poor prognosis in cervical carcinoma from TCGA. Conversely, the ability of cell proliferation and cell migration were reversed in LOXL2 knock-down cervical cell lines via regulating the genes’ expression of EMT phenotype in vitro. Overall, we demonstrated the correlation between LOXL2 expression status and cancer molecular characterizations of cervical carcinoma, and identified LOXL2 may serve as a therapeutic target for such carcinoma.